Travel & Tourism : A2 level for Edexcel - Dale, Gillian, 1955- (Oxford : Heinemann, 2006)
Provides two candidate handbooks to match the specifications of Edexcel and OCR for A2 Level GCE Travel and Tourism. Each book contains colourful photographs, illustrations, and activities and exercises for candidates to learn how to apply theory to real-life contexts.
"Endorsed by Edexcel."
Includes bibliographical references and index.
A2.
Keywords: Tourism; Tourism -- Problems, exercises, etc